Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae) - Petitpierre, Eduard; Anichtchenko, Alexander (Zootaxa, 2018)
Contrary to the subtle differences of habitus found between many species of Timarcha their internal sacs of male genitalia have shown a remarkable variation. Thirty-two Palaearctic taxa, mostly from the Iberian Peninsula, have been analyzed for this trait, which can be used for species diagnosis and also for establishing species groups of close relatedness in agreement mainly with genetic analyses. According with this trait, new synonymies and taxonomical changes are proposed: T. intermedia carmelenae Petitpierre, 2013 stat. nov., T. intermedia kiesenwetteri Kraatz, 1879 stat. nov., T. intermedia lugens Rosenhauer, 1856 stat. nov.; T. sinuatocollis monserratensis Bechyné, 1962 comb. nov.; T. piochardi Fairmaire, 1874 stat. nov.; T. tortosensis Bechyné, 1948 stat. nov.; T. perezii Fairmaire, 1884 syn. nov. and T. asturiensis Kraatz, 1879 syn. nov. = T. geniculata Germar, 1824. Furthermore, the endophalli of T. hummeli, T. carmelenae, T. kiesenwetteri, T. lugens, T. tenebricosa, T. parvicollis, T. insparsa, T. marginicollis, T. balearica, T. strangulata spp., T. calceata, T. scabripennis, T. espanoli, T. monticola, T. cyanescens, T. interstitialis, T. aurichalcea, T. oblongula, T. hispanica and T. granadensis are illustrated. One new species, T. aitanae sp. nov. is described.